The effect of fiber content on cotton reinforced albumen composites - Yusof, Yusliza; Ahmad, Zuraida (IIUM Press, 2011)
The effect of fiber content on mechanical properties and thermal stability of the cotton/albumen composites (CAC) were investigated and presented in this paper. The composites having 0%, 3%, 6%, 10%, 13 %, and 16% w/w of cotton fiber were considered. Hands lay-up technique was used to prepare the CAC specimens and dried for 24 hours before characterised and evaluated for their mechanical performance. The structure and thermal stability of the composites were characterized by using x-ray and thermogravimetry analysis, respectively. The tensile strength and impact resistance of CAC are found maximum with the value of 8.7 MPa and 19.0 kJ/m2, respectively. Analysis on the morphological structure by SEM revealed that the mechanical properties of the composites depend on good wettability and adhesion between fiber/matrix.